Developing Consensus-Based Priority Outcome Domains for Trials in Kidney Transplantation: A Multinational Delphi Survey With Patients, Caregivers, and Health Professionals. Issue 8 (August 2017) - Sautenet, Bénédicte; Tong, Allison; Manera, Karine E.; Chapman, Jeremy R.; Warrens, Anthony N.; Rosenbloom, David; Wong, Germaine; Gill, John; Budde, Klemens; Rostaing, Lionel; Marson, Lorna; Josephson, Michelle A.; et al.
Abstract : Background: Inconsistencies in outcome reporting and frequent omission of patient-centered outcomes can diminish the value of trials in treatment decision making. We identified critically important outcome domains in kidney transplantation based on the shared priorities of patients/caregivers and health professionals. Methods: In a 3-round Delphi survey, patients/caregivers and health professionals rated the importance of outcome domains for trials in kidney transplantation on a 9-point Likert scale and provided comments. During rounds 2 and 3, participants rerated the outcomes after reviewing their own score, the distribution of the respondents' scores, and comments. We calculated the median, mean, and proportion rating 7 to 9 (critically important), and analyzed comments thematically. Results: One thousand eighteen participants (461 [45%] patients/caregivers and 557 [55%] health professionals) from 79 countries completed round 1, and 779 (77%) completed round 3. The top 8 outcomes that met the consensus criteria in round 3 (mean, ≥7.5; median, ≥8; proportion, >85%) in both groups were graft loss, graft function, chronic rejection, acute rejection, mortality, infection, cancer (excluding skin), and cardiovascular disease. Compared with health professionals, patients/caregivers gave higher priority to 6 outcomes (mean difference of 0.5 or more): skin cancer, surgical complications, cognition, blood pressure, depression, and ability to work. We identified 5 themes: capacity to control and inevitability, personal relevance, debilitating repercussions, gaining awareness of risks, and addressing knowledge gaps. Conclusions: Graft complications and severe comorbidities were critically important for both stakeholder groups. These stakeholder-prioritized outcomes will inform the core outcome set to improve the consistency and relevance of trials in kidney transplantation. Abstract : Clinical trials report a variety of clinical, surrogate, or patient-reported outcomes. This article describes the results of novel methods using iterative Delphi Surveys of not only health professionals but patients and caregivers to determine the most important clinical trial outcome endpoints among both groups. Supplemental digital content is available in the text.